Survei Aplikasi E-learning untuk Mendukung Proses Belajar Mengajar pada Institusi Pendidikan Menggunakan Standar Kualitas ISO/IEC 9126 - Yenita Dewi Nurseha; Latifa Nurrachma Pradany (Universitas Multimedia Nusantara, 2014)
The need of e-learning nowadays has become the main concern of education institutions. For an organization, resources availability is crucial investment to be considered. Although the use of e-learning mushrooming, there are some critics on the quality of e-learning system. To know the quality of a system, we need a quality measurement. ISO 9126 is an international standard quality which is well known for its’ robustness and had been implemented in many applications. In this paper, the quality survey in some e-learning products been done, i.e. eFront and Moodle. The result show us that eFront system has 0.962745 quality value, better than Moodle which has 0.90925 quality value. Index Terms - E-Learning, eFront, ISO 9126, quality Moodle.